(untitled) (Olhar de Professor, 2022)
The National Curricular Common Basis (BNCC) of high school it’s the document that prescribes the curriculum policy of this phase and it has been the target of countless criticism, mainly because it clashes with the versions that constituted its construction process. From that, this article aims to identify and problematize the main ruptures in the BNCC/EM constructional historical process, as well as the displacement in the content of the texts that preceded. For that, it took as a theoretical-methodological perspective the way of thinking and doing research of Michel Foucault, more precisely the concept of problematization. It was found that the constructional process of BNCC/EM was permeated by different forces and political conflicts that ended up directly influencing the final version of the document. The light of the ruptures and displacements that constituted the BNCC/EM (2018), concluded the necessity to resist the educational project that the current curriculum policy prescribes for us.